The Relationship Between Learning Material Needs and the Interests of Participants in the Ikhwanul Muslimin Religious Study Group in Padang - Sarah Devina; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research was carried out due to the low level of participants’ interest in engaging in majelis taklim activities. This situation is assumed to arise from the lack of alignment between the learning materials delivered and the actual needs of the participants. The study aimed to identify the types of learning materials expected by participants, to describe their level of interest in attending the activities, and to analyze the relationship between these variables. A quantitative design with a correlational approach was applied in this study. The entire population, consisting of 25 participants, was involved as the research sample. Data were collected using questionnaires and analyzed through percentage calculations and the Spearman Rank correlation method. The findings revealed that the learning materials provided had not fully met the participants’ needs, and their level of interest in attending the activities tended to be low. In addition, the analysis showed a significant relationship between the relevance of learning materials and participants’ interest in participation. These results suggest that improving the suitability of learning materials based on participants’ needs can enhance their engagement in majelis taklim activities.Keywords: Learning material needs, participants’ interest, majelis taklim